Keanekaragaman Jenis Mangrove Di Pesisir Pantai Kelurahan Dowora Kecamatan Tidore Timur Kota Tidore Kepulauan Sebagai Bahan Ajar Poster - Abdullah, Nurdianti Hi; Juniartin, Juniartin; Muna, Lintal (Alpatih Harapan Semesta, 2023)
Mangrove forests are tropical ecosystems with significant ecological, social, and economic benefits. This ecosystem has unique characteristics due to the complex interactions between its constituent components. This research aims to: (1) analyze the diversity of mangrove species on the coastal shores of Dowora Village, Tidore Islands City as poster-based teaching materials in the subject of biodiversity; (2) identify the types of mangroves present in the area; and (3) evaluate the feasibility of the poster teaching materials based on the research results. The method used is Research and Development (R&D) with the Borg & Gall approach and the quadrant or plot method for data collection. The research results show that there are four types of mangroves in the area, namely Rhizophora apiculata, Bruguiera gymnorhiza, Sonneratia alba, and Ceriops tagal, with different diversity indices. The highest diversity index was obtained by Rhizophora apiculata (5.064), while Sonneratia alba and Bruguiera gymnorhiza had indices of 1.456 and 1.396, respectively, and Ceriops tagal had an index of 1.268. The validation of the poster teaching materials by content experts reached a validity level of 75% (fairly valid), while the validation by media experts reached 98% (very valid). These results indicate that the poster teaching materials are suitable for use as a learning medium for biodiversity based on the mangrove ecosystem.